2022
DOI: 10.1530/raf-22-0007
|View full text |Cite
|
Sign up to set email alerts
|

The future of diagnostic laparoscopy – Cons

Abstract: Endometriosis has a large impact on the lives of patients, affecting nearly 90% of women with chronic pelvic pain and infertility. Unfortunately, diagnosis for this condition is often delayed by an average of 7 years, with adolescent patients experiencing disproportionate delays, which can lead to disease progression. This is in part due to the use of an invasive procedure for primary diagnosis and limited access to subspecialty care. While laparoscopy serves an important purpose in the diagnosis and managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Molecular imaging could also play a key role in surgeries for endometriosis. Indeed, intraoperative imaging tools capable of visualizing endometriosis lesions could reduce operator bias during both laparoscopic diagnoses and surgical resections ( 19 ). Along these lines, a 2021 study by Al-Taher et al.…”
Section: Endometriosismentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular imaging could also play a key role in surgeries for endometriosis. Indeed, intraoperative imaging tools capable of visualizing endometriosis lesions could reduce operator bias during both laparoscopic diagnoses and surgical resections ( 19 ). Along these lines, a 2021 study by Al-Taher et al.…”
Section: Endometriosismentioning
confidence: 99%
“…The data demonstrated that [ 18 F]FES PET/CT fully agreed with histology and showed greater accuracy than MRI for lesions: PET/CT correctly identified 9 of 9 lesions, whereas MRI produced 3 false negatives and 3 false positives(3).Molecular imaging could also play a key role in surgeries for endometriosis. Indeed, intraoperative imaging tools capable of visualizing endometriosis lesions could reduce operator bias during both laparoscopic diagnoses and surgical resections(19). Along these lines, a 2021 study by Al-Taher et al compared intraoperative near-infrared fluorescence imaging with indocyanine green and conventional whitelight laparoscopy for the delineation of endometriosis lesions in a cohort of 15 patients (20).…”
mentioning
confidence: 99%
“…The procedure enables the identification of abnormalities and provides a means to determine the underlying causes of symptoms such as pelvic pain or infertility. As an alternative to traditional exploratory surgery, diagnostic laparoscopy minimizes invasiveness, accelerates recovery, and plays a pivotal role in the early and precise diagnosis of various gynecological conditions [ 4 ].…”
Section: Reviewmentioning
confidence: 99%